2015
DOI: 10.1186/s12969-015-0059-z
|View full text |Cite
|
Sign up to set email alerts
|

No association of IL-12p40 pro1.1 polymorphism with juvenile idiopathic arthritis

Abstract: BackgroundIL-12p40 plays an important role in the activation of the T-cell lines like Th17 and Th1-cells. Theses cells are crucial in the pathogenesis of juvenile idiopathic arthritis. A polymorphism in its promoter region and the genotype IL12p40 pro1.1 leads to a higher production of IL-12p40. We studied whether there is a difference in the distribution of the genotype in patients with JIA and the healthy population.MethodsIn 883 patients and 321 healthy controls the IL-12p40 promoter genotype was identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…STAT4 is mainly expressed in myeloid cells and is the transcription factor downstream of IL-12, which has been identified as a potential biomarker in sJIA, but has not been discussed as a potential therapeutic target so far [ 16 18 ]. We have previously shown that the likelihood of the occurrence of a polymorphism enhancing IL-12 expression was somewhat higher in patients with sJIA compared to other forms of JIA, which points toward IL-12 being more prominent in sJIA than previously thought [ 19 ]. In our array analysis, IL-12 was not differentially expressed; however, the IL-23 receptor, which is involved in IL-12 downstream signaling was downregulated in active disease (fold change 2.5, p = 0.012, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…STAT4 is mainly expressed in myeloid cells and is the transcription factor downstream of IL-12, which has been identified as a potential biomarker in sJIA, but has not been discussed as a potential therapeutic target so far [ 16 18 ]. We have previously shown that the likelihood of the occurrence of a polymorphism enhancing IL-12 expression was somewhat higher in patients with sJIA compared to other forms of JIA, which points toward IL-12 being more prominent in sJIA than previously thought [ 19 ]. In our array analysis, IL-12 was not differentially expressed; however, the IL-23 receptor, which is involved in IL-12 downstream signaling was downregulated in active disease (fold change 2.5, p = 0.012, Fig.…”
Section: Discussionmentioning
confidence: 99%